1973
DOI: 10.1099/00221287-78-2-253
|View full text |Cite
|
Sign up to set email alerts
|

The Growth Response of Cellulolytic Acetate-utilizing and Acetate-producing Butyrivibrios to Volatile Fatty Acids and Other Nutrients

Abstract: S U M M A R YThe growth responses of 33 strains of cellulolytic butyrivibrios, isolated from the rumens of sheep fed on low-protein teE hay diets, to various combinations of volatile fatty acids (VFA) have been determined. Propionate alone was generally retardatory to the acetate-utilizing strains whilst acetate was stimulatory .Branched-chain VFA were generally stimulatory to those strains on which propionate had a retardatory effect, and retardatory to those strains on which propionate had no effect. Propion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

1975
1975
2008
2008

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 20 publications
(12 reference statements)
0
17
0
Order By: Relevance
“…Shane et al (1969) have classified Butyrivibrio isolates into two groups: (1) the acetate-utilizers and (2) the acetate-producers. Roche et al (1973) found that propionate generally is inhibitory to the acetate-utilizing strains and stimulatory to the acetate-producing strains. In the fermentation of carbohydrates, group 1 produces a high amount of lactate but low levels of formate, whereas group 2 makes little lactate and more formate.…”
Section: 4lc Anaerobic Cellulolytic Bacteria Of Rumen and Intestinalmentioning
confidence: 97%
“…Shane et al (1969) have classified Butyrivibrio isolates into two groups: (1) the acetate-utilizers and (2) the acetate-producers. Roche et al (1973) found that propionate generally is inhibitory to the acetate-utilizing strains and stimulatory to the acetate-producing strains. In the fermentation of carbohydrates, group 1 produces a high amount of lactate but low levels of formate, whereas group 2 makes little lactate and more formate.…”
Section: 4lc Anaerobic Cellulolytic Bacteria Of Rumen and Intestinalmentioning
confidence: 97%
“…The effect of pH control in increasing the yields of bacteria has been described (see, for example, Kempe, Halvorson &Piret, 1950 andSargeant, 1968), but apart from effects on pH, both classes of compound have other effects on micro-organisms. Phosphates are essential in small quantities, but may be toxic in high concentration (Good et al 1966), whilst VFA salts have both inhibitory (Meynell, 1963 ;Hentges, 1967) and stimulatory (Bryant & Robinson, 1962;Roche et al 1973) effects on different micro-organisms under various conditions. Individual VFA may also have either inhibitory or stimulatory effects on the same bacteria, according to the concentrations of acid used (Hobson, Mann & Smith, 1963).…”
Section: Introductionmentioning
confidence: 99%
“…In agreement with that, in our P. ruminis strains, lactate production was associated with acetate utilization. Roche et al (1973) described these isolates as acetate-utilizing butyrivibrios. Lactate was also produced by B. fibrisolvens D1 T .…”
Section: Fermentation End Productsmentioning
confidence: 99%